Disorders of Endogenous and Exogenous Antioxidants in Neurological Diseases - Izabela Korczowska-Łącka; Bartosz Słowikowski; Thomas Piekut; Mikołaj Hurła; Natalia Banaszek; Oliwia Szymanowicz; Paweł P. Jagodziński; Wojciech Kozubski; Agnieszka Permoda-Pachuta; Jolanta Dorszewska (MDPI AG, 2023)
In diseases of the central nervous system, such as Alzheimer's disease (AD), Parkinson's disease (PD), stroke, amyotrophic lateral sclerosis (ALS), Huntington's disease (HD), and even epilepsy and migraine, oxidative stress load commonly surpasses endogenous antioxidative capacity. While oxidative processes have been robustly implicated in the pathogenesis of these diseases, the significance of particular antioxidants, both endogenous and especially exogenous, in maintaining redox homeostasis requires further research. Among endogenous antioxidants, enzymes such as catalase, superoxide dismutase, and glutathione peroxidase are central to disabling free radicals, thereby preventing oxidative damage to cellular lipids, proteins, and nucleic acids. Whether supplementation with endogenously occurring antioxidant compounds such as melatonin and glutathione carries any benefit, however, remains equivocal. Similarly, while the health benefits of certain exogenous antioxidants, including ascorbic acid (vitamin C), carotenoids, polyphenols, sulforaphanes, and anthocyanins are commonly touted, their clinical efficacy and effectiveness in particular neurological disease contexts need to be more robustly defined. Here, we review the current literature on the cellular mechanisms mitigating oxidative stress and comment on the possible benefit of the most common exogenous antioxidants in diseases such as AD, PD, ALS, HD, stroke, epilepsy, and migraine. We selected common neurological diseases of a basically neurodegenerative nature.